Development of a Science Literacy Test for Junior High School Students Based on the PISA 2025 Framework - Valio, Farah Amara; Safira, Ledya; Aulliyah, Uunwanah Agustin; Suwarna, Iwan Permana (FKIP Universitas Lampung, 2025)
This study aims to develop a valid, reliable, and practical science literacy test instrument based on the PISA 2025 framework as a tool for assessing the science literacy abilities of junior high school students in a contextual and in-depth manner. The issue of low science literacy in Indonesia, where 53.60% of students are in the very low category, highlights the urgency of providing an evaluation instrument that can comprehensively represent scientific thinking abilities. This achievement is closely related to the lack of student training using international assessment-based testing instruments such as PISA during the learning process. The research method used was Research and Development (R&D) with a 4-D development model (Define, Design, Development, Dissemination). The instrument was developed based on four dimensions of science literacy (competence, context, knowledge, and cognitive level) within the PISA 2025 framework and covers topics in the science subject, namely electricity, waves, and magnetism. Content validation was conducted by content, instrument, and language experts, while empirical testing was carried out to evaluate the quality of the test items. The research results showed that the instrument had high content validity (CVI = 0.93; CVR = 0.8–1). The average validity of each item reached 0.60. The instrument showed good consistency in terms of reliability, as indicated by the Omega McDonald coefficient of 0.79 for the combination of essay and complex multiple-choice questions, and the Cronbach’s Alpha value of 0.68 for multiple-choice questions analysed separately. Most items were categorized as moderately difficult (72.73%) and had good discriminative power (63.63%). Additionally, the practicality value of 78.85% indicates that the instrument is easy to use in an educational context. Therefore, this instrument is suitable for use as a science literacy assessment tool aligned with the PISA 2025 framework and supports the development of higher-order thinking skills in national assessments. Keywords: science literacy, instruments, assessment, PISA.